Performance Analysis of Wind Power Generation Models Using Oscillating Water Column - Susastro Susastro; Ardi Noerpamoengkas; Miftahul Ulum; Gatot Setyono (Universitas Muhammadiyah Purwokerto, 2020)
In this global era there are many resources that can be used one of them is, renewable resources such as sea waves. waves can be used as a generated of electrical energy. electrical energy that utilizes the occurrence of sea waves now can be applied in developed and developing countries. One method of conversion that can be done to convert wave energy into electrical energy is by using an oscillating water column. In this research, the turbine of oscillating water column was made using turbine wells with variations in rotation at 40, 50 and 58.3 rpm. the results it’s power of turbine, power of generator and efficiency system. The method used is the experimental method by testing the prototype using a low water wave on a laboratory scale. The results obtained from the experiment are that the electric power at the maximum load generated by the generator is 0.002875 Watt at a rotation of 50 rpm. While the lowest electric power at maximum load is 0.0004 W with a rotation of 40 rpm. The maximum efficiency of the system at load is 4.691% which occurs at a rotation of 50 rpm